The Politics of Women's Suffrage Local, National and International Dimensions - Hughes-Johnson, Alexandra; Jenkins, Lyndsey (New Historical Perspectives, 2021)
From 1832 to the present day, from the countryside in Wales to the Comintern in Moscow, from America to Finland and Ireland to Australia, from the girls' school to the stage, women's suffrage was the most significant challenge to the constitution since 1832, seeking not only to settle demands for inclusion and justice but to expand and redefine definitions of citizenship. This collection advances ongoing debates within suffrage history whilst also drawing on a range of new sources, different intellectual techniques and methodological approaches, which challenge established interpretations. With its focus on politics and political activism in its broadest sense, this collection makes a timely and substantial contribution to understanding the meaning of politics and political activism across the UK (and indeed, across the world) in this period, particularly as defined and experienced by women at the grassroots. This collection is a reminder of the ways in which women have often encountered and battled a hostile political climate, but pushed forward with determination, skill, tenacity and optimism: resonating with the renewed interest in women's history and feminist politics today.